Proliferation of Toxoplasma gondii (RH strain) is inhibited by the combination of pravastatin and simvastatin with low concentrations of conventional drugs used in toxoplasmosis - Sanfelice, Raquel Arruda; Bosqui, Larissa Rodrigues; da Silva, Suelen Santos; Miranda-Sapla, Milena Menegazzo; Panagio, Luciano Aparecido; Navarro, Italmar Teodorico; Conchon-Costa, Ivete; Pavanelli, Wander Rogério; Almeida, Ricardo Sergio; Costa, Idessania Nazareth (Journal of Applied Biomedicine, 2018)
Toxoplasma gondii, an etiologic agent of toxoplasmosis, is an obligate intracellular parasite, which exhibits an apicoplast organelle which assists in the metabolism of isoprenoids and other pivotal mediators for the parasite survival. Statins are drugs that inhibit cholesterol synthesis, blocking the conversion of the substrate HMG-CoA to mevalonate, thus preventing the initial processes of the biosynthesis of these precursors, both in humans and parasite. In the light of this information, we determined the effect of pravastatin and simvastatin associated with the current drugs (pyrimethamine and sulfadiazine) as a possible alternative treatment for this infection. Cytotoxicity was evaluated in HeLa cells by MTT assay, which was observed the drug combinations did not affect cell viability. HeLa cells (105) were infected with T. gondii tachyzoites of RH strain (5 × 105) and treated with pravastatin and/or simvastatin combined with pyrimethamine and/or sulfadiazine for 24 h. Our data showed a significant reduction in cell adhesion, infection and mainly parasite proliferation in all treatments. Based on these results, the combination of statins with drugs used in current therapy showed to be a promising therapeutic alternative for toxoplasmosis treatment.
Keywords: pyrimethamin; Cell Proliferation; statiny; Drug Synergism; kombinovaná farmakoterapie; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Toxoplasmosis; apikoplasty; synergismus léků; Apicoplasts; proliferace buněk; In Vitro Techniques; sulfadiazin; HeLa buňky; Drug Therapy, Combination; HeLa Cells; Sulfadiazine; toxoplazmóza; Antiprotozoal Agents; antiprotozoální látky; Toxoplasma; Pyrimethamine; techniky in vitro